Relationship between MC4R rs17782313 Polymorphism and Body Mass Index and Appetite Regulation in Young Adults in Indonesia - Sidarta, Erick; Kumala, Meilani (Faculty of Medicine, Universitas Diponegoro, 2025)
Background: Obesity is an increasing public health problem, including among young adults in Indonesia. Genetic, environmental, and behavioral factors contribute to obesity. One of the genetic variants associated with obesity is the MC4R rs17782313 polymorphism, which plays a role in appetite regulation and energy balance.Objective: This study aims to determine the relationship between the MC4R rs17782313 polymorphism and Body Mass Index (BMI) in young adults in Indonesia and to evaluate its effect on feelings of hunger, satiety and eating satisfaction.Method: We conducted a cross-sectional study involving 152 young adults at Universitas Tarumanagara. Genotyping was done using the real-time PCR method with the KASP™ system. To evaluate hunger, satiety, and eating satisfaction, we used the Visual Analog Scale (VAS; 0–100 mm, where lower scores indicate intense sensations of hunger, satiety, and satisfaction) before and after meals and calculated the difference scores. We analyzed the data using R software.Results: The results showed no significant relationship between the MC4R rs17782313 polymorphism and BMI (p = 0.7). However, there was a significant difference in hunger scores between the TT and TC genotypes (p = 0.024), where individuals with the TT genotype experienced a greater reduction in hunger after eating than individuals with the TC genotype. In addition, we also found a significant difference in BMI based on gender in our young adult population (p = 0.0032).Conclusion: This study found that MC4R rs17782313 was not significantly associated with BMI in this population. However, the variant may influence appetite regulation, as individuals with the TT genotype showed a smaller reduction in hunger after eating. A significant BMI difference between sexes was also observed; these findings suggest a role for MC4R in eating behavior, warranting further investigation in larger, diverse populations.